2017
DOI: 10.1002/ps.4776
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of field‐evolved resistance to Bacillus thuringiensis‐derived Cry1F δ‐endotoxin in Spodoptera frugiperda populations from Argentina

Abstract: CONCLUSION: This study is the first documented confirmation and characterization of S. frugiperda Cry1F field-evolved resistance in Argentina. The resistance to Cry1F in S. frugiperda populations collected in Argentina, is autosomal and incompletely recessive similar to the resistance reported in Brazil.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
101
1
1

Year Published

2019
2019
2020
2020

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 129 publications
(104 citation statements)
references
References 31 publications
1
101
1
1
Order By: Relevance
“…The fall armyworm, Spodoptera frugiperda (J.E. Smith) (Lepidoptera: Noctuidae: Noctuinae), is one of the most infamous insect pests due to an extremely high-level of polyphagy (more than 353 host-plants belonging to 76 plant families are reported 11 ), high dispersal capacity and migratory behavior 12 , the rapid development of insecticide resistance 13,14 , including resistance to Bt proteins [15][16][17][18] , and occasional outbreaks 19 . The FAW is native to North and South America, and its presence in West Africa was first reported in 2016 20 .…”
Section: Textmentioning
confidence: 99%
“…The fall armyworm, Spodoptera frugiperda (J.E. Smith) (Lepidoptera: Noctuidae: Noctuinae), is one of the most infamous insect pests due to an extremely high-level of polyphagy (more than 353 host-plants belonging to 76 plant families are reported 11 ), high dispersal capacity and migratory behavior 12 , the rapid development of insecticide resistance 13,14 , including resistance to Bt proteins [15][16][17][18] , and occasional outbreaks 19 . The FAW is native to North and South America, and its presence in West Africa was first reported in 2016 20 .…”
Section: Textmentioning
confidence: 99%
“…Laboratory studies have also indicated resistance of FAW to YieldGard VT PRO maize that expresses Cry1A.105 and Cry2Ab2, PowerCore containing Cry1A.105, Cry2Ab2 and Cry1F, and Agrisure Viptera and Agrisure Viptera 3 that express Vip3Aa20 and Vip3Aa20/Cry1Ab, respectively . FAW also evolved resistance to Cry1F maize in Puerto Rico, in some areas of the southeastern USA, and Argentina …”
Section: Introductionmentioning
confidence: 99%
“…At present, a number of field-evolved resistant populations of fall armyworm have been detected, including resistance to a variety of chemical pesticides and Bt crops, and the level of resistance is increasing [25][26][27][28][29] . The mechanisms of resistance to pesticides are mainly due to variation in receptor genes, such as amino acid mutations in the ryanodine receptor (RyR) (diamide), acetylcholinesterase (AChE) (organophosphate), voltagegated sodium channel (VGSC) (pyrethroids), and so on [30][31][32] .…”
Section: Introductionmentioning
confidence: 99%